Decoding our DNA : Craig Venter vs. the Human Genome Project - Ballen, Karen Gunnison (Scientific rivalries and scandals., 2013)
Explores human gene mapping, the history of the Human Genome Project, and the resulting feud between the HGP and Craig Venter, a scientist originally on the project that left to research on his own.